2022
DOI: 10.1155/2022/9539286
|View full text |Cite
|
Sign up to set email alerts
|

The Combinatory Effect of Spirulina Supplementation and Resistance Exercise on Plasma Contents of Adipolin, Apelin, Ghrelin, and Glucose in Overweight and Obese Men

Abstract: Introduction and Objective. Researchers are considering combining exercise and supplementation as a new strategy for weight loss and obesity prevention. This study is aimed at evaluating the effect of eight weeks of circuit resistance training and spirulina supplementation on plasma levels of adipolin, apelin, ghrelin, and glucose in overweight and obese men. Methods. The current investigation was conducted in a single-blind and quasiexperimental fashion. Sixty overweight and obese men ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…Past studies have shown that spirulina has an anti-obesity effect, similar to regular exercise, by activating the AMPK pathway and increasing sirtuin-1 (SIRT1) on the muscle tissue [20,23,33]. In fact, AMPK regulates NF-kappa B (NF-kB), Forkhead box protein O1 (FOXO1) and peroxisome proliferator-activated receptor gamma (PPAR-γ) by regulating SIRT1 activity, which leads to an increase in adiponectin and leptin hormones, which has a positive effect on reducing fat mass [23,31,34]. It is possible that the lower level of ASP in the training plus spirulina group is due to a greater decrease in appetite, calorie intake, weight and MBF in this group compared to other groups.…”
Section: Asp and Body Composition Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies have shown that spirulina has an anti-obesity effect, similar to regular exercise, by activating the AMPK pathway and increasing sirtuin-1 (SIRT1) on the muscle tissue [20,23,33]. In fact, AMPK regulates NF-kappa B (NF-kB), Forkhead box protein O1 (FOXO1) and peroxisome proliferator-activated receptor gamma (PPAR-γ) by regulating SIRT1 activity, which leads to an increase in adiponectin and leptin hormones, which has a positive effect on reducing fat mass [23,31,34]. It is possible that the lower level of ASP in the training plus spirulina group is due to a greater decrease in appetite, calorie intake, weight and MBF in this group compared to other groups.…”
Section: Asp and Body Composition Resultsmentioning
confidence: 99%
“…Every session included 12 movements that participants followed very low, low, moderate, or high intensity exercise in every movement. Details of the CRT program is shown in Tables 1 and 2 [23]. Each training session was started with warm-up and nished with cooldown (10 minutes).…”
Section: Exercise Intervention Protocolmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the intervention duration and sample size were higher than ours, and such differences may be explanatory factors for the insignificant results for fullness, desire to eat, and satiety, while the scores for hunger and ability to eat were reduced. Investigations into the effect of Spirulina on leptin and ghrelin, as hormones that regulate satiety and hunger, have yielded mixed results (Kaka et al, 2019 ; Mohammad et al, 2022 ), and generally did not support appetite reducing effects. Thus, further studies assessing the impact of Spirulina on the appetite‐related hormones are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Investigations into the effect of Spirulina on leptin and ghrelin, as hormones that regulate satiety and hunger, have yielded mixed results (Kaka et al, 2019;Mohammad et al, 2022), and generally did not support appetite reducing effects. Thus, further studies assessing the impact of Spirulina on the appetite-related hormones are needed.…”
Section: Effect Of Spirulina Sauce On Appetitementioning
confidence: 99%